The Effect of Potato Drying Time and The Ratio of Wheat Flour With Potato Flour on The Quality of Potato Cookies - Aprilia S.K.Y. Simamora; Ismed Suhaidi; Era Yusraini (Jurnal Rekayasa Pangan dan Pertanian, 2014)
Potato consists of high moisture that has highly caused of  damage effect and consist of lower starch than the other sweetpotato. Cookies is a kind of food with a low moisture so that has a longer storage period. The aim of this research was to find the best time of drying of potato for making potato flour and the ratio of wheat flour with potato flour on the quality of potato cookies. This research was performed by using completely randomized design with two factors, i.e : potato drying time (L) : (4 hours, 4,5 hours, 5 hours and 5,5 hours) and the ratio of wheat flour and potato flour (P) : (80%:20%, 60%:40%, 40%:60% and 20%:80%). Parameters analyzed were moisture content, protein content, ash content, volume expansion, fat content, fiber content, hedonic values of flavor and taste, score values of color and texture. The result showed that the drying time of potato had highly significant effect on moisture content, fat content, fiber content, hedonic values of flavor, hedonic values of taste and score values of color. The ratio of wheat flour with potato flour had highly significant effect on moisture content, protein content, ash content, volume expansion, hedonic values of taste, score values of color and score values of texture. Interaction of the two factors had no significant effect on all parameters except moisture content. The drying of 4,5 hours or the ratio of wheat flour and potato flour of (80%:20%) produced the best quality of potato cookies.   Keywords: Cookies, drying time, potato flour, quality